2021
DOI: 10.1039/d0nj05143h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antibacterial applications of pyrazolyl-sulfonamides and their palladium complexes

Abstract: A series of pyrazolyl sulfonamide compounds were prepared by a multi-step procedure involving preparation of phenyl pyrazolyl compounds (C1, C2) and their chlorosulfonated derivatives (C3-C5), which were then converted to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Complex one demonstrated notable antibacterial activity against B. subtilis and S. aureus, consistent with Amoah et al [ 138 ]. These authors suggested that metal complexes penetrate and disrupt bacterial cell walls [ 139 ].…”
Section: Resultssupporting
confidence: 88%
“…Complex one demonstrated notable antibacterial activity against B. subtilis and S. aureus, consistent with Amoah et al [ 138 ]. These authors suggested that metal complexes penetrate and disrupt bacterial cell walls [ 139 ].…”
Section: Resultssupporting
confidence: 88%
“…Another problem is that the ink cannot be erased permanently. There are some methods in which water is used for writing and erasing, [41,[48][49][50][51] however the use of azo dyes for inkless writing and erasing has emerged recently. [52,53] Consequently, we aimed to develop rewritable paper strip or erasable inks using HDBS because of the added advantages of reducing paper waste and chemical pollution.…”
Section: Real-world Applications Of Hdbsmentioning
confidence: 99%
“…In this respect, transition metal complexes are promising sources for new antimicrobials as they offer augmented electronic properties and a rich variety of three-dimensional structures if compared to their organic counterparts. According to the literature, a number of complexes of transition metals (including Mn, Cu, Zn, Ru, Rh, Pd, Ag, Ir, Pt, Au, etc .) were shown to possess antibacterial properties, with few of them that reached the clinical use. However, many opportunities offered by the application of inorganic chemistry to this field of research remain unexplored.…”
Section: Introductionmentioning
confidence: 99%